Problem-Based Learning to Support Creative Thinking Skills in Automotive Engineering Students: A Classroom Action Research Study - ilham yuliady; Zulfadli Zulfadli; Erik Fernandez; Yogi Dian Alfana (AEEJ : Journal of Automotive Engineering and Vocational Education, 2026)
Low creative thinking skills in automotive engineering learning can limit students’ ability to generate, adapt, and elaborate technical solutions. This study described the implementation of Problem-Based Learning (PBL) and examined changes in students’ creative thinking skills in the Fundamentals of Automotive Engineering course. A Classroom Action Research design was used with 21 Automotive Engineering students and conducted in two cycles consisting of planning, action, observation, and reflection. Data were collected using observation sheets on creative thinking indicators and analyzed descriptively based on creativity categories. In the pre-cycle condition, most students were classified as fairly creative (52.38%), while only 4.76% were very creative. After PBL implementation in Cycle II, the creative category increased to 47.62% and the very creative category increased to 28.57%, while the least creative category decreased to 0%. These findings suggest that PBL can support the development of students’ creative thinking in automotive engineering learning.